Neuro-navigation: Equipment, Tips, and Tricks on Brain Navigated Surgery - Enoh Nkongho Kingsly; Ismail Bozkurt; Bipin Chaurasia (Indian Journal of Neurosurgery, 2023)
Neuronavigation is a system composed of advanced intraoperative equipment where a virtual link is created between digital images and anatomical structures such that intra-axial lesions are precisely located and removed safely and efficiently. Thus, neuronavigation has enormously increased the success rate of brain and spinal cord surgery compared to the era in which it did not exist. This article takes a look at and emphasizes, as a reminder, the benefits of neuronavigation, equipment used, equipment setup, tips and tricks on preoperative preparation of patients' images, and future perspectives on neuronavigation and equipment, aspects that are very rare in literature. A commonly used neuronavigation system is described, with regard to its parts, setup, instructions, and tips and tricks. This narrative review allows the reader to grasp the main aspects of neuronavigation, the functions of all the aspects, and what to expect during brain surgery. Although training with neuronavigation is a given in most developed parts of the world, in underdeveloped and developing countries the lack of equipment does not allow most neurosurgeons to have a first-hand experience. This article has aimed to ease the learning curve for neurosurgeons that are unfamiliar with neuronavigation.